The Impact of Protozoan Predation on the Pathogenicity of Vibrio cholerae - Espinoza-Vergara, Gustavo; Hoque, M. Mozammel; McDougald, Diane; Noorian, Parisa (Frontiers in Microbiology, 2020)
In the aquatic environment, Vibrio spp. interact with many living organisms that can serve as a replication niche, including heterotrophic protists, or protozoa. Protozoa engulf bacteria and package them into phagosomes where the cells are exposed to low pH, antimicrobial peptides, reactive oxygen/nitrogen species, proteolytic enzymes and low concentrations of essential metal ions such as iron. However, some bacteria can resist these digestive processes. For example, Vibrio cholerae and Vibrio harveyi can resist intracellular digestion. In order to survive intracellularly, bacteria have acquired and or developed specific factors that help them to resist the unfavourable conditions encountered inside of the phagosomes. Many of these intra-phagosomal factors used to kill and digest bacteria are highly conserved between eukaryotic cells and thus, are also expressed by the innate immune system in the gastrointestinal tract as the first line of defense against bacterial pathogens. Since pathogenic bacteria have been shown to be hypervirulent after they have passed through protozoa, the resistance to digestion by protist hosts in their natural environment plays a key role in enhancing the infectious potential of pathogenic Vibrio spp. This review will investigate the current knowledge in interactions of bacteria with protozoa and human host to better understand the mechanisms used by both protozoa and human hosts to kill bacteria and the bacterial response to them.